# I have a few more questions that I either need help with or just need checking.

Is the algebraic expression a polynomial? if it is write the polynomial in standard form,

1. 6x-9+8x^2 I got Yes; 8x^2+6x-9

Perform the indicated operations. Write the resulting polynomial in standard for.

3. (9x^5+20x^4+10) -(4x^5-10x^4-19) I got 5x^5+30x^4+29

Factor out the greatest common factor.

1. x^2(x-3)-(x-3) I got x^2(x-3)

Factor the trinomial, or state that the trinomial is prime.

3. x^2-4x-32 I got (x-4)(x-8)

4. 7x^2+39x+20 I got (7x+4)(x+5)

Factor the differnce of two squares.

7. 4x^2-49y^2 I got (2x+7y)(2x-7y)

Factor the perfect square trinomial.

10. x^2+10x+25 I got (x+5)^2

Factor using the formula for the sum or difference of two cubes.

13. x^3-8 This one I don't understand

14. 27x^3+64 This one I don't understand.

Factor completely, or state that the polynomial is prime.

21. 9x^4-9 This one I don't undertand

Factor and simplify the algebraci expression.

25. x^5/6 - x^1/6 This one I don't understand.

for

Factor out the greatest common factor.

1. x^2(x-3)-(x-3) I got x^2(x-3)

The greatest common factor would be (x-3)

The factored form would be:

(x-3)(x^2 - 1)

=(x-3)(x+1)(x-1)

"13. x^3-8 This one I don't understand

14. 27x^3+64 This one I don't understand."

For these two, there is an actual formula for the sum and difference of two cubes.

A^3 + b^3 = (A+B)(A^2 - AB + B^2) and

A^3 - b^3 = (A-B)(A^2 + AB + B^2)

so (x^3-8) = (x-2)(x^2+2x+4)

try the next one

"21. 9x^4-9 This one I don't undertand "

Factor out the 9 as a common factor, then you are left with a difference of squares

"25. x^5/6 - x^1/6 This one I don't understand. "

Tricky one.

How about taking out a common factor of x^(1/6)

x^5/6 - x^1/6

= x^(1/6)(x^(4/6) - 1)

= x^(1/6)(x^(2/3) - 1)

= x^(1/6)(x^(1/3) + 1)(x^(1/3) - 1)

(x^3-8) = (x-2)(x^2+2x+4) How did you come up with this? I get that you had to use the formula, but don't understand how you came up with the answer.

21. 9x^4-9= This is what I did for this one: 9(x^4-1)= (x^2+1)(x^2-1)= 9(x^2+1)(x^2-1).

25. x^5/6 - x^1/6 On this one, its a multiple choice question and x^1/6(x^1/3+1)(x-^1/3-1) is not a choice, but x^1/6(x^2/3-1 is a choice.

The choices are: a. x^5/6(1-x^2/3), b. x^1/6(x^5-1), c. x^1/6(x^2/3-1), d. x(x^2/3-1)

Sorry, my sister changed my screen name.

"(x^3-8) = (x-2)(x^2+2x+4) How did you come up with this? I get that you had to use the formula, but don't understand how you came up with the answer."

Look at the formula for

A^3 - B^3

Both of these must be perfect cubes.

The first factor is (A-B) in other words, the cube roots of those two terms

We had x^3 - 8

the cube root of x^3 is x of course, and the cube root of 8 is 2

For the second factor you just use A=x and B=2 to finish it.

for #21 you had

9(x^4-1)= (x^2+1)(x^2-1)= 9(x^2+1)(x^2-1).

the last part can be taken one more step, you have the difference of squares.

Final answer:9(x^4-1)= (x^2+1)(x^2-1)= 9(x^2+1)(x-1)(x+1).

for #25 I had x^1/6(x^2/3-1) as my second last line.

I simply took it one more step recognizing a difference of squares.

Since they allowed fractional exponents in their given answer, they should have allowed my final answer.

I need some help with some problems as well as need some checked. Could you please help me? Thanks!

1. How do you graph y=1/x

2. How do I the x and y intecepts using a graph?

Solve and check the linear equation.

9. (-4x-2)+7=-3(x+3) I got 14

10. -2[7x-7-6(x+1)]=2x+5 I got 21/4

Solve the equation.

13. (x+7)/4=2-(x-1)/6 I am not too sure how to do this one.

Find all the values of x satisfying the given conditions.

16. y1= (x+6)/3, y2=(x+8)/6, and y1=y2 This one I don't understand.

First write the value(s) that make the denominator(s) zero. Then solve the equation.

19. (x-8)/2x +5= (x+6)/x This one I also don't understand.

Determine whether the equation is an identity, a conditional equation, or inconsistent equation.

24. -2(x+7)+52=4x-6(x+3) I got Inconsistent

25. (3x+2)/4 +2= -7x/2 I got inconsistent

## 1. To graph y=1/x, you can start by creating a table of values. Choose some x-values, and then calculate the corresponding y-values by substituting the x-values into the equation. Once you have a few points, plot them on a graph. Also, include the point (0,0) since x cannot be zero in the equation.

2. To find the x-intercepts, set y=0 in the equation and solve for x. These are the points where the graph intersects the x-axis. To find the y-intercept, set x=0 and solve for y. This is the point where the graph intersects the y-axis.

Checking your solutions:

9. (-4x-2)+7=-3(x+3)

Simplifying both sides:

-4x + 5 = -3x - 9

Combining like terms:

x = -14

10. -2[7x-7-6(x+1)]=2x+5

Simplifying both sides:

-14x + 14 + 12x + 12 = 2x + 5

Combining like terms:

-2x + 26 = 2x + 5

Combining like terms again:

4x = 21

Dividing by 4:

x = 21/4

13. (x+7)/4=2-(x-1)/6

Multiply both sides by the least common denominator, which is 12:

3(x+7) = 24 - 2(x-1)

Simplify both sides:

3x + 21 = 24 - 2x + 2

Combining like terms:

5x + 19 = 26

Combining like terms again:

5x = 7

Dividing by 5:

x = 7/5

16. y1 = (x+6)/3, y2 = (x+8)/6, y1 = y2

Setting the two equations equal to each other:

(x+6)/3 = (x+8)/6

To eliminate the fractions, multiply both sides by 6:

2(x+6) = x+8

Simplifying both sides:

2x + 12 = x + 8

Combining like terms:

x = -4

19. (x-8)/2x + 5 = (x+6)/x

Multiplying both sides by 2x to eliminate fractions:

(x-8) + 5(2x) = (x+6)(2x)

Expanding and simplifying:

x - 8 + 10x = 2x^2 + 12x

Combining like terms:

11x - 8 = 2x^2 + 12x

Rearranging and combining like terms again:

2x^2 + x - 8 = 0

This is a quadratic equation that can be factored or solved using the quadratic formula.

24. -2(x+7) + 52 = 4x - 6(x+3)

Simplifying both sides:

-2x - 14 + 52 = 4x - 6x - 18

Combining like terms:

-2x + 38 = -2x - 18

Adding 2x to both sides:

38 = -18

This is a contradiction, so the equation is inconsistent. There is no solution.

25. (3x+2)/4 + 2 = -7x/2

Multiplying through by 4 to eliminate fractions:

3x + 2 + 8 = -14x

Combining like terms:

3x + 10 = -14x

Adding 14x to both sides:

17x + 10 = 0

Subtracting 10 from both sides:

17x = -10

Dividing by 17:

x = -10/17

Please note that it's always a good idea to double-check your work and solutions to make sure they are correct.